Molecular Evaluation for Drought Tolerant Using Marker Assisted Breeding Method - Fatimah, Fatimah; Prasetiyono, Joko; Trijatmiko, Kurniawan Rudi; Sustiprijatno, Sustiprijatno (BRIN, 2018)
The sustainability and increasing the national rice production require the readiness of food and agriculture sector cope with the impacts of climate change, land degradation, drought area, sloping production and the raising of population growth. Adaptation plays an important role in ensuring the sustainability of food security. This research aimed to develop drought-tolerant variety of Inpari 30 (submergence tolerance variety) and Situ Bagendit through marker-assisted backcrossing-through pyramiding gene of identified QTLs for foreground selection and to explore SSRs and 6K SNPs for background selection distributed in 12 rice chromosome of drought tolerant donor (Cabacu) and recipient rice (Inpari 30 and Situ Bagendit). The foreground selection revealed that flanking SSRs of each QTLs (qRPF2.1, qGPP2.1, qSPP4.1 and Sub1) was less than 2 cM. The background selection through polymorphic survey of Rice 6K SNP primers revealed 2457 (53,3%) polymorphic SNPs on Inpari 30 vs Cabacu and 2563 (55,6%) polymorphic SNPs on Situ Bagendit vs Cabacu with the average distance about 0.74 cM/chromosome. The genotypic selection of F1 Inpari 30/Cabacu and F1 Situ Bagendit/Cabacu have already in heterozygote condition for these 4 QTLs target. These lines was continued for backcross breeding to develop BC1F1 Inpari 30/Cabacu and BC1F1 Situ Bagendit/Cabacu generation.